Postgenomics : perspectives on biology after the genome - Richardson, Sarah S., 1980-; Stevens, Hallam (Duke University Press, 2015)
The contributors to Postgenomics assess the changes to the life sciences the Human Genome Project's completion brought, develop new frameworks for studying the human genome in the postgenomic era, and show how the environment, technology, race, and gender influence the genome and how we think about it.